Comprehensive diversification measure of diversification strategies and performance of selected firms - Asrarhaghighi, Ebrahim (2013)
Product and international diversified firms play a significant role in the world economy. Therefore, assessing the relationship between diversification and performance has attracted a lot of attention for decades. However, the results of the studies are inconclusive. Researchers have mentioned this inconclusiveness might be a result of diversification measurement problems and using different measures of diversification.The main problems for product diversification measures are about capturing the relatedness among a firm’s activities based on the relatedness among the firm’s resources and multidimensionality of relatedness. The main problems for international diversification measures are around capturing the multidimensionality of international diversification, the breadth and depth, and its relatedness. The Total Global Diversification Index as the most comprehensive measure of diversification that capture both product and international dimensions of diversification , has some of the above mentioned problems. Therefore, by using the Inter industry Relatedness Index, new measures of product diversification were designed. Afterward, a new comprehensive measure of diversification was constructed by integrating the new measures of product diversification which can capture the relatedness among firm’s resources and multidimensionality of relatedness and,the Degree of Internationalization measure which is a multidimensional measure of international diversification and can capture the relatedness and breadth and depth of international diversification. To find the superiority of the new measure, its predictive validity was tested against the total global diversification index through assessing the relationship between diversification and performance for U.S. largest firms. The result showed that the new measure has higher predictive validity. Moreover, it was found that product diversification does not have an effect on firms’ performance but it positively moderates the relationship between international diversification and performance. Also, a sigmoid relationship between international diversification and market based measure of performance was found. The developed measure of diversification may assist researchers to assess the relationship between diversification and performance by a new comprehensive measure which has higher predictive validity. Also, practitioners can use the new measure to trace the results of their firms’diversification strategies over years and compare it to their competitors.